The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1742-1241.2009.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior or concomitant seasonal influenza vaccination on MF59-adjuvanted H1N1v vaccine (Focetria™) in adult and elderly subjects

Abstract: One dose of MF59-adjuvanted H1N1v vaccine met the licensure criteria for adult and elderly subjects 3 months after seasonal vaccination, or concomitantly with seasonal vaccine in adults, without impacting the tolerability or immunogenicity of either vaccine, thus facilitating mass influenza immunisation campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 9 publications
2
21
1
Order By: Relevance
“…Coinciding with the current influenza pandemic, caused by the new emergent A/H1N1 influenza viral strain, this characteristic has been demonstrated for the new MF59-adjuvanted A/H1N1 monovalent pandemic vaccine (Focetria ® , Novartis Vaccines, Italy), which has shown optimal immunogenicity in healthy adults, at a 7.5 μg antigen dosage. 40,41 The same is valid for another adjuvanted influenza vaccine, developed using an innovative adjuvant system, called AS03. This tocopherol oil-in-water emulsion-based adjuvant system has been tested, during the last few years, in a candidate H5N1 pre-pandemic influenza vaccine and has recently been adopted in the licensed formulation of a current A/H1N1 pandemic vaccine (Pandemrix ® , Glaxo Smith Kline, Germany): good Table 2.…”
Section: Critical Issues Desideratamentioning
confidence: 85%
See 1 more Smart Citation
“…Coinciding with the current influenza pandemic, caused by the new emergent A/H1N1 influenza viral strain, this characteristic has been demonstrated for the new MF59-adjuvanted A/H1N1 monovalent pandemic vaccine (Focetria ® , Novartis Vaccines, Italy), which has shown optimal immunogenicity in healthy adults, at a 7.5 μg antigen dosage. 40,41 The same is valid for another adjuvanted influenza vaccine, developed using an innovative adjuvant system, called AS03. This tocopherol oil-in-water emulsion-based adjuvant system has been tested, during the last few years, in a candidate H5N1 pre-pandemic influenza vaccine and has recently been adopted in the licensed formulation of a current A/H1N1 pandemic vaccine (Pandemrix ® , Glaxo Smith Kline, Germany): good Table 2.…”
Section: Critical Issues Desideratamentioning
confidence: 85%
“…Results showed that one dose of MF59-adjuvanted A/H1N1 monovalent vaccine, at a 7.5 μg antigen dosage, or even at the lower dose of 3.75 μg, with a half dose of MF59, provides protection for the majority of adults and elderly subjects, meeting the CHMP criteria for pandemic influenza vaccine licensure. 41 Although an exact evaluation of the effectiveness, offered by the influenza vaccines, is difficult to establish, some useful data concerning the clinical impact of the MF59-adjuvanted vaccine are available in the elderly. In particular, the effectiveness of the MF59-adjuvanted influenza vaccine has been demonstrated in older adults, thus avoiding emergency admissions for pneumonia including influenza B viruses of the B/Victoria and B/Yamagata lineages in future influenza vaccine preparations.…”
Section: -81mentioning
confidence: 99%
“…Therefore seasonal TIV is generally not expected to confer a significant degree of cross-protection to pH1N1 [35]. Only older age by way of exposure to pre-1957 influenza strains has consistently been found to confer a relevant degree of cross-reactive antibodies to pH1N1 [17], [36][39]. In this respect it is interesting that we found that seasonal TIV was more likely to induce cross-reactive antibodies to pH1N1 in older than in younger subjects, which contradicts the conclusion of Hancock et al who found that seasonal TIV induces little to no cross-reactive antibody response to pH1N1 in any age group.…”
Section: Discussionmentioning
confidence: 99%
“…Five vaccines were authorised by the European Medicines Agency (EMA) for use in the European Union [4]. Clinical trials reported high immunogenicity of the adjuvanted vaccines [5-10]; post-marketing studies [11-16] showed an effectiveness on preventing confirmed pH1N1 that was similar to that of seasonal influenza vaccines in well matched years [11,17]. So far, only limited and varying results have been reported on the effectiveness of the adjuvanted vaccines in preventing severe disease of pH1N1 that required hospitalisation [13,14,18].…”
Section: Introductionmentioning
confidence: 99%